Impact of olive oil usage on physical properties of chocolate fillings - Dias, João (2016)
The development of a new olive oil based chocolate filling was carried out. In this study three different types of virgin olive oil were tested, in three different concentrations in the production of chocolate fillings. An instrumental analysis was carried out for chemical analyses, such as moisture and pH. The color analysis included the CIE 1976 L*a*b* color space and RGB color space. The rheological analysis included the evaluation of flow curve, flow index (n), consistency (K) and dynamic moduli (G’ and G’’). No influence was detected on the moisture or pH of chocolate fillings, due to the concentration or type of olive oil. However, the use of olive oil decreased consistency from 1371 Pasn to 148 - 559 Pasn, even using olive oil concentrations of 20% w/w. Also, G’ registered a similar correlation, where a decrease was observed from 4.42 x 106 Pa to values around 1.70-2.51 x 106 Pa, for 20% w/w olive oil. The fillings presented a darker yellow-green color when using olive oil produced with Galega and Cordovil de Serpa varieties, but olive oil produced with the Arbequina variety did not affect color significantly, although further studies will be required to evaluate the impact of ripening stage.